Inhibition of growth of nonbasal planes in ice by fish antifreezes. - Raymond, J A (1989)
Peptide and glycopeptide antifreezes from a variety of cold-water fishes cause ice single crystals grown from the melt to assume unusual and strikingly similar habits. The antifreezes inhibit growth on the prism faces but allow limited growth on the basal plane. As new layers are deposited on the basal plane, pyramidal surfaces develop on the outside of the crystal, and large hexagonal pits form within the basal plane. The pits are rotated 30 degrees with respect to the normal orientation of hexagonal ice crystals. Growth inhibition on the prism, pyramidal, and pit faces indicates that these faces contain sites of adsorption of the antifreeze molecules. Several properties of the antifreeze pits are consistent with (but do not prove) an origin of the pits at dislocations. The similarity of crystal habit imposed on ice by antifreezes with wide differences in composition and structure indicates a common mechanism.